(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
assisting techniques of the Answer / University of Nahrain. Twenty-four (24) male animals were used from Rattas rattas to investigate the effect of different concentrations of lead acetate on some blood parameters. The animals were randomly distributed into four groups, each containing 6 animals. First group (control) was injected intraperitoneal with a dose of 0.1 ml of normal physiological saline (NaCl). Lead acetate was injected intraperitoneal of the second group with a dose 1 mg/kg body weight, and the third group with a dose 2 mg/kg body weight, and the fourth group with a dose 3 mg/kg body weight. The dose was given between one day another for 48 days (24 doses). The results of the study showed a significant decrease (p<0.05) in the concentrations of hemoglobin, the total number of white blood cells, the total number of red blood cells. While the study showed no difference (p<0.05) in erythrocyte sedimentation rate (ESR). In conclusion the present study showed the exposure to different concentrations of lead acetate has a detrimental effect on some physiological blood parameters, and directly proportional to the increase concentration of lead acetate and exposure period.